Effect of tapered magnetic field on expanding laser-produced plasma for heavy-ion inertial fusion. (20th December 2016) - Kanesue, T.; Ikeda, S.
Abstract: A laser ion source (LIS) is a promising candidate as an ion source for heavy-ion inertial fusion (HIF), where a pulsed ultra-intense and low-charged heavy ion beam is required. It is a key development for a LIS to transport laser-produced plasma with a magnetic field to achieve a high-current beam. The effect of a tapered magnetic field on laser-produced plasma is demonstrated by comparing the results with a straight solenoid magnet. The magnetic field of interest is a wider aperture on a target side and narrower aperture on an extraction side. Based on the experimentally obtained results, the performance of a scaled LIS for HIF was estimated.